2014
DOI: 10.1186/s40478-014-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of α-synuclein in dementia with Lewy bodies is associated with decline in the α-synuclein-degrading enzymes kallikrein-6 and calpain-1

Abstract: Kallikrein-6 and calpain-1 are amongst a small group of proteases that degrade α-synuclein. We have explored the possibility that reduction in the level or activity of these enzymes contributes to the accumulation of α-synuclein in Lewy body diseases. We measured calpain-1 activity by fluorogenic activity assay, kallikrein-6 level by sandwich ELISA, and levels of α-synuclein and α-synuclein phosphorylated at serine 129 (α-synuclein-P129), in post-mortem brain tissue in pure dementia with Lewy bodies (DLB, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 57 publications
(84 reference statements)
1
30
2
Order By: Relevance
“…Supporting the model, several studies have shown the presence of neuropathological thalamic alterations in DLB and PDD along with altered GABAergic and cholinergic receptors and structural and cellular abnormalities of the thalamic nuclei . Interestingly, a recent review extensively analyzed the role of α7 nicotinic receptor activity of TRN neurons in theproduction of DLB hallucinations .…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the model, several studies have shown the presence of neuropathological thalamic alterations in DLB and PDD along with altered GABAergic and cholinergic receptors and structural and cellular abnormalities of the thalamic nuclei . Interestingly, a recent review extensively analyzed the role of α7 nicotinic receptor activity of TRN neurons in theproduction of DLB hallucinations .…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
“…Supporting the model, several studies have shown the presence of neuropathological thalamic alterations in DLB and PDD along with altered GABAergic and cholinergic receptors and structural and cellular abnormalities of the thalamic nuclei. [124][125][126][127][128][129][130][131][132] Interestingly, a recent review extensively analyzed the role of α7 nicotinic receptor activity of TRN neurons in theproduction of DLB hallucinations. 133 Of note, the presence of DMN decoupling along with signs of primary thalamic degeneration has also been observed in frontotemporal dementia patients carrying the C9orf72 mutation, a condition characterized by severe psychosis.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
“…Extracellular species of both oligomeric and fibrillar α-syn can be internalized and induce intracellular seeding aggregation in cultured cells [6, 15, 16]. Such effects can be potentiated by failure in the proteasomal [17, 18] or lysosomal [19] degradation systems or by reduced levels/activity of intra- and extracellular proteases [20]. Despite the increased knowledge in this field, our understanding of the roles of different α-syn aggregates for the propagation of pathology in Lewy body disorders remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…α‐syn and α‐syn‐P129 levels were measured by sandwich ELISA in GuHCl‐solubilized brain tissue extracts and SH‐SY5Y cell lysates, as previously described (Miners et al . ,b; Swirski et al . ) For the α‐syn ELISA, a mouse monoclonal anti‐α‐syn antibody (Syn‐1, raised against epitope corresponding to aa 91–99 (Perrin et al .…”
Section: Methodsmentioning
confidence: 99%
“…We reported previously that the levels of CAPN‐1 and KLK6 are reduced in the cingulate cortex in DLB (Miners et al . ).…”
mentioning
confidence: 97%